Research priorities in the management of severe Plasmodium falciparum malaria in children. - Idro, R; Aketch, S; Gwer, S; Newton, C; Maitland, K (2006)
Severe malaria is a common reason for admission to paediatric wards in hospitals across sub-Saharan Africa. Despite over 100 years of research, mortality remains high. Deaths are associated with severe metabolic acidosis, shock, severe anaemia, hypoglycaemia, impaired consciousness, raised intracranial pressure, and status epilepticus. Most inpatient deaths occur within 24 h of admission to hospital, before the beneficial effects of treatment with antimalarial drugs are achieved. This review covers the priority areas for research in the care of children with severe malaria, addressing each of the main risk factors associated with death, in a bid to reduce the inpatient mortality.